Nosocomial dissemination of hypervirulent Klebsiella pneumoniae with high-risk clones among children in Shanghai - Du, Qingqing; Pan, Fen; Wang, Chun; Yu, Fangyuan; Shi, Yingying; Liu, Wenxin; Li, Zhi; He, Ping; Han, Dingding; Zhang, Hong (Frontiers in Cellular and Infection Microbiology, 2022)
Objectives: Clinical, molecular and phenotypic surveillance of hypervirulent Klebsiella pneumoniae (hvKp) strains among children will facilitate implementation of tailor-made infection-control measures for the special population. Methods: Non-repetitive K. pneumoniae (Kp) strains consecutively collected during 2019-2020 were screened for hypervirulence genes (prmpA, prmpA2, iucA, iroB, and peg344) using PCR. Positive strains were further characterized by four phenotypic assays (string test, serum killing assay, siderophore production, Galleria mellonella lethality assay), followed by murine sepsis model to determine virulence in vitro and in vivo. Also, capsular types, sequence types, plasmid replicon types, antimicrobial resistance determinants and susceptibility were analysed. Results: A total of 352 isolates were collected, wherein 83 (23.6%) were hypervirulence genes-positive Kp (hgKp). A significant increase in KPC-2-producing KL47-ST11 among hgKp strains was observed, from 5.3% (1/19) in 2019 to 67.6% (25/37) in 2020 (P<.0001), suggesting the potential dissemination of the hybrid virulence and carbapenem-resistance encoding plasmid among children. Further, hgKp isolates were classified into hvKp (n = 27) and hgKp-low virulence (hgKp-Lv) (n = 56) based on virulence phenotypic assays. In hvKp, diverse genetic clones were observed and K1-ST23 or K2-ST25 strains with sensitivity to multiple antibiotics were prevalent (25.9%, 7/27). Compared with hgKp-Lv, hvKp infection had a higher propensity to involve severe pneumonia (22.2% vs. 12.5%) in elder children and significant higher mortality in mice (P = 0.0086). Additionally, either hvKp or hgKp-Lv infections were mostly healthcare-associated and hospital-acquired (74.1% vs. 91.9%). Conclusions: These data suggest that K1-ST23 and K2-ST25 were high-risk clones of hvKp, and the genetic convergence of virulence and carbapenem-resistance was increasing among children. Control measures are needed to prevent the dissemination in clinical settings.